Comparison of Manipulative Indicators of Students and Therapists Using a Robotic Arm: A Feasibility Study - Koike Yuji; Okino Akihisa; Takeda Kazuhisa; Takanami Yasuhiro; Toyohiro Hamaguchi (Applied Sciences, 2021)
In this study, the motion therapy elements necessary for student education were clarified through comparison of the therapeutic motion techniques of therapists and students using an educational arm robot (Samothrace: SAMO). Eight therapists and 25 fourth-year students participated. The therapeutic motion therapy task was a reciprocating exercise in which the elbow joint of SAMO was flexed from an extended position and then re-extended. This was performed for three types of muscle tone intensities (mild, moderate, and severe), and the peak velocity, angle ratio, velocity time, and movement time were recorded using SAMO. These data were then compared using analysis of covariance. It was found that the SAMO elbow joint kinematic data generated by therapists differed significantly from those of students for different muscle tones. Multiple comparisons showed that the therapeutic motion techniques of students were associated with a higher peak velocity, smaller peak angle ratio, and shorter peak velocity time and movement time than those of the therapists. Thus, when students learn therapeutic motion techniques, they should be taught to (1) deal with multiple muscle tone intensities and (2) reduce the joint movement speed applied to the patient to extend the exercise time and ensure maximum joint movement range.